PENGARUH DOSIS PUPUK CAIR GREEN TONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L) - Yovita Yasintha Bolly; Oktaviana Rosario Sere Gili (Fakultas Pertanian, Universitas Nusa Nipa, 2023)
This study aimed to determine the effect of Green Tonik liquid fertilizer dosage on the growth and yield of mustard plants (Brassica juncea L.). The research was conducted in Watumilok Village, Kangae District, Sikka Regency from September to December 2022. The study used a Randomized Block Design (RBD) consisting of five treatments of Green Tonik liquid fertilizer dosage, namely without fertilizer (G0), 3 cc/liter of water/plant (G1), 4 cc/liter of water/plant (G2), 5 cc/liter of water/plant (G3), and 6 cc/liter of water/plant (G4) with four replications, resulting in 20 experimental units. The variables observed included plant height, number of leaves, and fresh weight of the plants. Data were analyzed using analysis of variance (ANOVA) and continued with the Least Significant Difference (LSD) test at the 5% significance level. The results showed that the application of Green Tonik liquid fertilizer had a highly significant effect on plant height, number of leaves, and fresh weight of mustard plants. The best result was obtained at a dosage of 5 cc/liter of water/plant with plant height of 27.93 cm, 9.7 leaves, and fresh weight of 362.50 g. Therefore, it can be concluded that the optimal dosage of Green Tonik liquid fertilizer to improve the growth and yield of mustard plants is 5 cc per liter of water per plant.